Identitas dan Seksualitas dalam Akun Instagram Waria_Vip - Giovani, Evelin; Rachmasari, Firtha Ayu; Istiqomah, Nurul; Sijabat, Survey (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This research aimed to look at identity and sexuality in the social media Instagram account of waria_vip. The cyber world was currently often used as a medium for spreading sexual content and as a medium for promoting prostitution. One account that used social media as a platform for existence was waria_vip which offered promotion services for transgender accounts that open prostitution services. The Waria_vip account had becoming a catalog containing photos of transgender vying to attract followers and users of their services. The uploaded photos feature photos of transvestites in vulgar and seductive poses to attract new followers to their account. The method used in this research was a qualitative approach with Maxwell's concept of cybersex. Cybersex was a form of transformation of the satisfaction of sexual desire which marks a change in culture related to sexuality which transformed to futuristic era because the fulfillment of sexual desire had been separated from space and time. Social media such as Instagram was becoming the perfect platform for transgender people to exist because identity and sexuality in social media were fluid.